Effect of Spraying and Mesh Size on Surface Roughness of SS400 Steel Sandblasting Process - Aldio, Rieza Zulrian; Dedikarni; Saputra, Budi (Journal of Renewable Energy and Mechanics, 2021)
During this time the ship's hull often occurs due to corrosion levels of salt in the Indonesian sea varies. The repair process often done to overcome this problem is by sandblasting which aims to clean the metal from the surface of the rust and provide suitable surface roughness on the metal surface so that the coating material can stick properly. This study aims to determine the size of silica sand and the repetition of the sandblasting process on the value of surface roughness and cleanliness of the material. In this study the SS400 material was sandblasting using 12 mesh, 16 mesh and 20 mesh sand at 7 bar, spraying 1x and 2x. From the test results obtained at a particle size of 20 mesh, 7 bar pressure, repeated spraying 2x which results in a surface roughness of 19.80 µm and cleanliness results achieved according to standard SA 2 1/2 (SSPC-SP10) from these conditions obtained surface roughness values according with the standard surface roughness of sandblasting and the level of cleanliness achieved in accordance with ISO 8503 standards and has been allowed for application.